The Effectiveness of Project-Based Learning Integrated with Historical Methods in Improving Students' Historical Thinking Skills - B. Fitri Rahmawati; Muhammad Shulhan Hadi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
Historical thinking is one of the primary objectives of contemporary history education. However, empirical studies consistently indicate that students’ historical thinking skills remain limited because history instruction is still dominated by the transmission of factual, text-oriented knowledge. Therefore, an instructional model that promotes historical thinking is needed. This study examines the effectiveness of a Project-based Learning (PjBL) model integrated with historical methods in improving students’ historical thinking skills. A quasi-experimental study employing a non-equivalent control group design was conducted with 124 eleventh-grade students. Data were collected through classroom observations, project-task analysis, and historical thinking tests, and analyzed using an independent-samples t-test with SPSS 25.0. The findings revealed a significant difference between the experimental and control groups (t (122) = 7.083, p < 0.001), indicating that the integrated PjBL model effectively enhanced students’ historical thinking skills. This study contributes to history education by providing empirical evidence that integrating Project-based Learning with the historical method offers an effective pedagogical approach for fostering historical thinking, thereby extending the application of PjBL beyond content mastery toward disciplinary historical reasoning.